Akselarasi Financial Technology Untuk Meningkatkan Omset UMKM Kuliner Kota Padang Pasca Pandemi Covid 19 - Yenni Del Rosa; Idward Idward; Tiara Turay (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2023)
The purpose of the study was to determine the effect of financial technology acceleration on the turnover of culinary SMEs in Padang. The research data comes from primary data in the form of a questionnaire given to the owners of culinary SMEs in the city of Padang. This research uses associative method with quantitative approach. The research population was 371 culinary SMEs in the city of Padang and samples were taken by purposive sampling 193 culinary SMEs. Collecting data using field research techniques, interviews, observations and questionnaires. All research variables meet all instrument tests and classical assumption tests. The research data was processed using inferential statistics with the results of multiple linear regression equations Y = 1.255 + 0.739X1 - 0.328X2 + 0.629X3 + 0.321X4 + 0.523X5 + 0.478X6 + 0.367X7 + 0.485X8 + e. Partial and simultaneous hypothesis testing at a significance level of 5% shows that business experience, fintech loan value, household financial liquidity, suitability of loan applications, suitability of business needs, usefulness of fintech and internet activities have a significant positive effect on the turnover of Padang culinary SMEs except the interest rate. fintech has a significant negative effect on the turnover of culinary SMEs in the city of Padang. Correlation of business experience, fintech interest rate, fintech loan value, household financial liquidity, suitability of loan applications, suitability of business needs, usefulness of fintech and internet activities with culinary MSME turnover = 0.596 (medium) and R2 = 0.359 and Adjusted R square = 0.350 The purpose of the study was to determine the effect of financial technology acceleration on the turnover of culinary SMEs in Padang. The research data comes from primary data in the form of a questionnaire given to the owners of culinary SMEs in the city of Padang. This research uses associative method with quantitative approach. The research population was 371 culinary SMEs in the city of Padang and samples were taken by purposive sampling 193 culinary SMEs. Collecting data using field research techniques, interviews, observations and questionnaires. All research variables meet all instrument tests and classical assumption tests. The research data was processed using inferential statistics with the results of multiple linear regression equations Y = 1.255 + 0.739X1 - 0.328X2 + 0.629X3 + 0.321X4 + 0.523X5 + 0.478X6 + 0.367X7 + 0.485X8 + e. Partial and simultaneous hypothesis testing at a significance level of 5% shows that business experience, fintech loan value, household financial liquidity, suitability of loan applications, suitability of business needs, usefulness of fintech and internet activities have a significant positive effect on the turnover of Padang culinary SMEs except the interest rate. fintech has a significant negative effect on the turnover of culinary SMEs in the city of Padang. Correlation of business experience, fintech interest rate, fintech loan value, household financial liquidity, suitability of loan applications, suitability of business needs, usefulness of fintech and internet activities with culinary MSME turnover = 0.596 (medium) and R2 = 0.359 and Adjusted R square = 0.350